RANCANG BANGUN ALAT UJI UNJUK KERJA TURBIN ULIR DENGAN SISTEM AKUISISI DATA UNTUK MEDIA PEMBELAJARAN PRAKTIKUM TURBIN AIR - Iswanda, Dovian; Suharto, Widodo Putra; Naufal, Alban; Andriani, Devi; Supandi, Supandi; Nurhaidah, Nurhaidah; Faino, Faino (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
To facilitate students' understanding of the types of water turbines, how they work, and the parameters that affect the performance of water turbines, it will be easier if the water turbine is made on a laboratory scale so that students can observe directly and students can change some parameters directly so that students understand the parameters that affect the performance of water turbines. In this research, a laboratory-scale screw turbine type water turbine will be made equipped with a data acquisition system where several sensors will be installed to read the parameters when the turbine is operating which then all parameters will be displayed on the LCD and recorded into memory automatically. This research was conducted using experimental methods by designing and manufacturing screw turbines using 3D Printing using digital prototyping techniques and designing a data acquisition system to facilitate parameter measurement. The results of the study obtained a screw turbine model with an outer diameter (Ro) of 0.07 m, an inner diameter (Ri) of 0.03 m, a pitch distance of 0.05 m, a thread length of 0.6 m, a maximum output power of 3.5 W at a discharge of 0.07 m3/s, maximum efficiency of 6 % at a discharge of 0.07 m3/s.